KEPEMIMPINAN KIAI DALAM MENGUATKAN SIKAP MODERASI SANTRI PONDOK PESANTREN RAUDLATUL MUTA’ALIMI WONOASIH PROBOLINGGO - Agung Agus Setiawan; Benny Prasetiya (IMTIYAZ: Jurnal Ilmu Keislaman, 2023)
This research aims to evaluate several aspects, namely: 1) How the role of Kiai leadership can strengthen the moderation attitude of students at the Raudlatul Muta'alimin Islamic Boarding School, 2) Concrete actions taken by Kiai leadership, 3) How Kiai leadership evaluates this process. The research method used is a qualitative approach with case studies. The data collection process involved interviews, observation, and document analysis. Data analysis was carried out through the steps of data condensation, data presentation, and drawing conclusions. Data validity is tested through the credibility, dependability and certainty of the data. The results of the research reveal several things, including: first, Kiai Pondok Pesantren Raudlatul Muta'alimin carries out his role as a leader with four main functions, including as a direction setter, agent of change, spokesperson and coach. Kiai use situational leadership styles, such as delegation, guidance, and direction, to achieve leadership effectiveness. Second, Kiai's efforts to form a moderation attitude among students involve studying the yellow book and emphasizing the curriculum. Third, the implementation of Kiai's leadership in strengthening the santri's moderation attitude at the Raudlatul Muta'alimin Islamic Boarding School went without significant obstacles, in line with Kiai's expectations, and the santri succeeded in internalizing the moderation attitude in their daily lives. Keywords:  Islamic Moderation; Islamic Boarding School Leader.